The Willow Project Under International Environmental Law: Legal Challenges and Global Climate Implications - Suparman, Suparman; Mastur, Mastur (UNISSULA, 2025)
This study examines the Willow Project, a major oil drilling initiative in Alaska, to assess its compatibility with international environmental law and its implications for global climate change. The research aims to determine whether the project aligns with the United States’ obligations under the Paris Agreement and key principles like the precautionary approach and international environmental responsibility. Utilizing a normative and comparative qualitative methodology, the study analyzes legal frameworks, international treaties, and the project’s environmental impacts. Findings indicate that the Willow Project significantly increases greenhouse gas emissions, undermining global climate goals and violating the principle of non-harm by risking transboundary environmental damage. These outcomes highlight a conflict between economic interests and environmental obligations, challenging the enforcement of international law. The study advocates for robust global policies, including stricter standards and enhanced monitoring, to ensure large-scale energy projects support climate change mitigation. By addressing these legal and environmental challenges, the research contributes to strengthening international governance to combat climate change effectively.